2017
DOI: 10.1371/journal.pone.0182680
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 signaling promotes epithelial-mesenchymal transition-like phenomena, cell motility, and cell invasion in synovial sarcoma cells

Abstract: The epithelial-to-mesenchymal transition (EMT) and the reverse process (the mesenchymal-to-epithelial transition [MET]) have been shown to be associated with tumor cell invasion and metastasis in different carcinomas. The EMT and MET have recently been shown to play a key role in the pathogenic processes of sarcomas, which are completely different from those of carcinomas. However, the definitive roles of the EMT in the tumorigenesis of synovial sarcomas remain unknown. Here, we explored whether transforming g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Dramatic responses were observed with this drug in cervical cancers and pancreatic cancers, with an ongoing study including multiple expansion cohorts . In sarcomas, the role of TGF‐β is largely unexplored, though importance of stromal impact and crosstalk has been theorized preclinically in synovial sarcomas and osteosarcomas, where TGF‐β could play an important role in metastasis …”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%
“…Dramatic responses were observed with this drug in cervical cancers and pancreatic cancers, with an ongoing study including multiple expansion cohorts . In sarcomas, the role of TGF‐β is largely unexplored, though importance of stromal impact and crosstalk has been theorized preclinically in synovial sarcomas and osteosarcomas, where TGF‐β could play an important role in metastasis …”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%
“…Historically, several stimuli from the local microenvironment, including growth factors and cytokines, inflammation, hypoxia, disruption of cell contact or contact with the surrounding ECM have been proposed as potential triggers of EMT. Although the molecular mechanisms underlying EMT in lung are still unclear, numerous studies have revealed that TGF-β signalling is a powerful inducer of EMT mostly through its canonical Smad-dependent pathway but also β-catenin signalling pathway seems to be involved [ 198 , 199 ]. This complex signalling network controls the expression of EMT markers.…”
Section: New Insights In Vitamin a Deficiency And Epithelial–mesenmentioning
confidence: 99%
“…However, it is still controversial how TGF-β acts on sarcomas. Qi et al (35,45) reported that the TGF-β/Smad/Snail signaling pathway is closely associated with EMT, which promotes cell proliferation, migration, and invasion in synovial sarcomas. Dwivedi et al (46) showed that TGF-β promotes cell migration by phosphorylating Smad2 and Smad3 in uterine carcinosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mechanism of EMT, transforming growth factor (TGF)-β, which has roles in cell proliferation, differentiation, and tumorigenesis, has been reported to be closely associated with EMT in many epithelial and mesenchymal tumors (34,35). We previously analyzed pathways that are regulated by CBR1 in a uterine cervical cancer cell line overexpressing CBR1 (21).…”
Section: Introductionmentioning
confidence: 99%